Unfit to Be a Slave: A Guide to Adult Education for Liberation - Vucaj, Indrit (Journal of Interdisciplinary Studies in Education, 2019)
Influenced by a mainstream radical ideology, Unfit to Be a Slave: A Guide to Adult Education for Liberation is unequivocally a democratic pillar of human consciousness. Unorthodoxy slants encouraging adult education as the locomotive to fit human consciousness into a capitalistic design are dissed at best. The author unapologetically calls for embracement of a new and radically revolutionary tenet aimed to liberate from captivity the conscious minds of human beings and seriously question the very foundation of the role of education in the lives of human beings. Humanistic and libertarian adult educators alike including liberals to some extent, who uphold the dignity and the autonomy of human beings (Elias & Merriam, 2005), appreciate the language and the tone the author uses throughout the text in support to human empowerment.